Compensation and Restorative Justice in Offences Against Women for Realization of SDGs: An Analysis of Grievance Redressal Mechanisms in the Criminal Justice System of Andhra Pradesh - Mowleeswari, G. Chandra; Babu, Botuku Ramesh; Kumar, Yagati Ashok; Varma, RS Harish Kumar; Snehalatha, S; Lakshmi, V Vijay (Journal of Cultural Analysis and Social Change, 2025)
This study examines the efficacy of the crime controlling laws and victim welfare policies together with the judicial decisions to identify the gaps in promotion of healing and reparation mechanism for elimination of offences against women and also to secure peace in the society, to fulfill the United Nation’s SDGs 5 and 16. Since the corresponding author is a Judicial Officer, and acquainted experience with examining victims of sexual offences while prosecution of offenders, Auto-ethnography method has been opted for study. Information from public domains, research publications, print media publications, and findings of the Judiciary, discussions with the Judicial Officers who had conducted trials of offences against women, has been collected as secondary source of information. Microsoft Excel was used for creating charts to present the data in an organized manner. The authors have reviewed literature, acknowledged the sources, made a systematic study of the information, and concluded to make the findings invaluable in this area. The study provides invaluable insights into the effectiveness of the grievance redressal mechanisms in realizing SDGs. The results observe that both the restorative justice system to which compensation is the key element, and retributive justice approach to which the punishment is the main component, are crucial for the Criminal Justice System for elimination of violence against women, to promote access to holistic justice, and to secure peace in society. The study underscores the significance of the offender-victim-community mediation for swift restoration of the victims, besides retributive justice for prevention of re-victimization of victims, and victimization of offenders.